Integrating skills by means of webquests to learn english - Faicán Baculima, Cecilia Fernanda; Garnica Barrera, Carmen Maribel
This work focused on how a technological strategy, a WebQuest, can develop the four language skills. This study comprised two parts. The first one included a field research regarding the use of WebQuests and the second one involved a development of three lessons based on WebQuests. For the initial part, a survey and interview were employed. Through these surveys it was found that WebQuests were not well-known among teachers. The interview showed that WebQuests are important strategies for students when learning a foreign language. Therefore, in the last part of this study, three lessons based on WebQuests were prepared to provide teachers with models that can be used with low levels. The purpose of these lessons was to integrate the four language skills.